PENERAPAN ANIMASI MACROMEDIA FLASH UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PADA MATERI TEKANAN - Abbas, Muhammad Luqman Hakim (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThe purpose of this study was to determine the increase in students' understanding of conceptson the subject of pressure. This study was included in an experimental study with a controlgroup pre-test-post-test design. The population in this study were all eighth grade students ofMTsN 4 Jombang. The sample in this study was class VIII-A which amounted to 35 students asthe experimental class and VIII-B totaling 38 students as the control class. The researchinstruments were in the form of learning media questionnaires and tests of students' conceptualunderstanding. Testing the hypothesis using the t-test. the calculation results obtained by tcount= 2.569 and t table = 2.065 with a significant level of 0.05. This shows that tcount> t table.Thus the application of macromedia flash animation has an effect on the results of learningphysics subject matter pressure.Keywords: macromedia flash animation, learning outcomes, pressure